The new legal conflicts involving labor aspects regarding the COVID-19 - Toyama Miyagusuku, Jorge (2020)
COVID-19 has changed the way we live and with it, the ways, conditions, and sanitary measures at work. In addition to these notable changes, this pandemic has created great uncertainty among the whole society and diverse questionings about its management in the workplace. Precisely, COVID-19 has caused an impact on the labour relationships, both in the modification of work systems, and the appearance of new legal conflicts involving labour aspects, mainly due to the spread of coronavirus in the workplace or on the occasion of the labours carried out by workers. The main conflicts are related to the matters of compensation for damages, challenge of dismissals, payment of social benefits, questioning of measures to suspend the working relationships between employers and employees, among others.